Effect of broccoli extract enriched diet on liver cholesterol oxidation in rats subjected to exhaustive exercise. Issue 169 (May 2017) - Cardenia, Vladimiro; Rodriguez-Estrada, Maria Teresa; Lorenzini, Antonello; Bandini, Erika; Angeloni, Cristina; Hrelia, Silvana; Malaguti, Marco
Graphical abstract: Highlights: The broccoli extract reduced cholesterol oxidation after exhaustive exercise. The broccoli extract enriched diet increased antioxidant phase 2 enzyme activity. Phytochemicals could be useful in the prevention of liver oxidative damage. Abstract: The effect of broccoli extract (BE)-enriched diet was studied in order to evaluate its ability to counteract liver cholesterol oxidation products (COPs) induced by acute strenuous exercise in rats. Thirty-two female Wistar rats were randomly divided into four groups: control diet without exercise (C), BE-enriched diet without exercise (B), control diet with acute exhaustive exercise (S) and BE-enriched diet with acute exhaustive exercise (BS). The study lasted 45 days and on the last day, rats of S and BS groups were forced to run until exhaustion on a treadmill. Glutathione-S-transferase (GST), glutathione reductase (GR), glutathione peroxidase (GPx), catalase (CAT) and cholesterol oxidation products (COPs) were determined in liver. Exhaustive exercise was clearly responsible for tissue damage, as evidenced by the increase of lactate dehydrogenase (LDH) plasma activity in the S group. Moreover, the exercise protocol reduced CAT activity in liver, while it did not affect GST, GR and GPx. BE-enriched diet raised GST, GR and CAT activities in rats of BS group. The main COPs found were 7α-hydroxycholesterol, 7β-hydroxycholesterol, 7-ketocholesterol, cholestanetriol, 24-hydroxycholesterol and 27-hydroxycholesterol. The BE-enriched diet led to reduced cholesterol oxidation following exhaustive exercise; the highest level of COPs was found in the S group, whereas the BS rats showed the lowest amount. This study indicates that the BE-enriched diet increases antioxidant enzyme activities and exerts an antioxidant effect towards cholesterol oxidation in rat liver, suggesting the use of phytochemicals in the prevention of oxidative damage and in the modulation of the redox environment.